The Effectiveness of Implementing a Marking Scheme in the Employee Performance Evaluation System at PT Telkom Indonesia (Persero) Tbk - Tantri Pebyani; Asri Sundari; Salma Aparatunisa; Eka Septiana; Muhammad Rizkie (Advances in Management & Financial Reporting, 2026)
Purpose: This study aims to analyze the representation of the marking scheme in the performance measurement system for the Board of Directors of PT Telkom Indonesia (Persero) Tbk based on company documents. Research Method: This study employed a descriptive qualitative approach using documentary analysis and qualitative content analysis. Secondary data were obtained from the 2024 Annual Report of PT Telkom Indonesia (Persero) Tbk, as well as the literature on performance appraisal, marking schemes, Organizational Justice Theory, and Agile Performance Management. The analysis was conducted through data reduction, open coding, categorization, interpretation, and triangulation of sources and theories. Results and Discussion: The research findings indicate that the Board of Directors’ KPIs are documented through five main perspectives, which are broken down into indicators, targets, weightings, and Talent Development. This structure reflects the key characteristics of a marking scheme as a documented evaluation framework. It is conceptually aligned with the principles of procedural justice and some characteristics of Agile Performance Management. However, this study does not evaluate the system’s implementation or user perceptions, as it relies solely on documentary data. Implications: The findings can serve as a reference for designing a performance measurement system based on documented indicators and as a foundation for further research using primary data. Originality: This study proposes using the marking scheme concept as a framework for analyzing the structure of the Board of Directors’ performance measurement system based on corporate documents.